2016
DOI: 10.1039/c5ra27785j
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of a food macromolecular assembly: the case of okra mucilage

Abstract: Isolation steps of okra hydrocolloid and its thermodynamic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Comparable trends on the projected area vs. hydration level have been reported for soya beans (Desphande et al, 1993) and for lentil seeds (C ß arman, 1996). Dimopoulou et al (2016) reported that the free energy associated with the solvation of macromolecules from the bulk of the okra fruit body is positive; that suggests that there is no spontaneity towards the en masse release of macromolecules to the aqueous phase. Ghori et al (2014) studied the swelling of okra extract-based pellets containing pharmaceutics and reported swelling within a few minutes (typically not more than 15-30 min), followed by a reduction in the extent of the swelling.…”
Section: Hydration and Swellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparable trends on the projected area vs. hydration level have been reported for soya beans (Desphande et al, 1993) and for lentil seeds (C ß arman, 1996). Dimopoulou et al (2016) reported that the free energy associated with the solvation of macromolecules from the bulk of the okra fruit body is positive; that suggests that there is no spontaneity towards the en masse release of macromolecules to the aqueous phase. Ghori et al (2014) studied the swelling of okra extract-based pellets containing pharmaceutics and reported swelling within a few minutes (typically not more than 15-30 min), followed by a reduction in the extent of the swelling.…”
Section: Hydration and Swellingmentioning
confidence: 99%
“…The differences between the two experimental sets were initially attributed to the inherent dissimilarities between cultivars. Recent thermodynamic measurements (Dimopoulou et al, 2016) and ongoing experiments all point to the importance of the prior status (history) of hydrogen bonding on the self-association of okra polymers. aqueous extraction.…”
Section: Extraction Of Mucilagementioning
confidence: 99%
See 2 more Smart Citations
“…Ραρατθρείται επίςθσ ότι τα ςωματίδια των εκχυλιςμάτων παρουςιάηουν ετερογζνεια ςε επίπεδο εκατοντάδων νανομζτρων. (Zaharuddin, Noordin, & Kadivar, 2014;Dimopoulou, Tsivintzelis, Ritzoulis, & Panayiotou, 2016).…”
Section: θλεκτρονικι μικροςκοπία ςάρωςθσ (Sem)unclassified